Uma escuta das migrações, músicos haitianos e performances em deslocamento - Stringini, Daniel (Farol, 2021)
In dialogue with Haitian musicians and ensembles in southern Brazil, I propose to listen to the city based on listening to these migrant flows. Following the paths and displacement of musicians and their music throughout the city, I reflect on the encounter and tensions between “migrating sound worlds” and “local sound worlds”. I suggest that black musical fronts in a mostly white city have produced new situations, pointed out questions and rearranged urban territories.